Effect of Credit Risk Management on the Performance of Commercial Banks in Rwanda: A Case of Cogebank Rwanda Plc - Nsabimana, Diogene; Kengere, Osiemo (Journal of Finance and Accounting, 2023)
The research focused on the effect of credit risk management on the performance of commercial banks in Rwanda. A case of Cogebank Rwanda PLC. The study specifically analysed the effects of credit appraisal, credit risks identification, credit risks monitoring and control and credit collection on the performance of Cogebank, Rwanda PLC. The study covered the period of four years from 2018 up to 2021. In term of research methodology, the study adopted a cross section research design and used questionnaire, interview and documentation as main tools of data collection. The study adopted censes approach and considered all 35 staff from two departments accounting and credit departments which were purposively selected. Researcher also analyzed the collected data using Statistical Product and Service Solutions (SPSS). The results showed that the bank granted loans of 95.8%; 97.3%; 92.4% and 85.0% respectively of their deposits from 2018 to 2021. And looking at BNR’s regulations on the loan granting it is clear that the commercial bank must not exceed 80% of deposit collected when granting loans. From 2018 up to 2021 the ratio of Return on Equity was as following: 12.62%; 13.63%; 12.24% and 13.79% respectively. The results show the value of adjusted R2 is 0.650 implying that there was a variation of 65% of performance of Cogebank Rwanda PLC which was explained by the four credit risk management strategies adopted by the bank namely credit risk appraisal, credit risk identification, credit risk analysis, and credit risk monitoring. This implies that, credit risk appraisal, credit risk identification, credit risk analysis, and credit risk monitoring explained 65% of performance at a confidence level of 95%. This study recommends that Cogebank Rwanda Plc should improve loan recovery procedures for better loan management, should improve the implementation of guarantee policies for better loan management and since the latter has significant effect on performance of the bank. Keywords: Credit Risk Management, Commercial Banks Performance, Cogebank Rwanda Plc. Rwandan Banking Sector, Financial Stability